Disillusionment and Decay: The American Dream in F. Scott Fitzgerald’s The Beautiful and the Damned - Meria Zakiyah Alfisuma; Tri Pujiati (Universitas Muhammadiyah Tangerang, 2026)
This qualitative descriptive study analyzes the portrayal of the American Dream through Anthony Patch in F. Scott Fitzgerald’s The Beautiful and the Damned. Set in the Jazz Age, a time of excess and cultural change, the novel exposes how materialism, social pressure, and moral decay corrupt the ideal of success. Using textual analysis and a sociocultural literary approach, the study examines Anthony’s pursuit of wealth and status without ethical foundation, leading to his downfall. The findings reveal how society and Gloria Gilbert influence Anthony’s values, showing his gradual disillusionment with the American Dream. This research contributes to cultural criticism of early 20th-century American literature and underscores the continued relevance of Fitzgerald’s critique in today’s consumer-oriented world